Faktor-Faktor Yang Mempengaruhi Prokrastinasi Akademik Mahasiswa Yang Mengikuti Organisasi: Sebuah Kajian Literatur - Candra Dinata, Komang Agung; Nurcahyo, Firmanto Adi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Procrastination is an act of postponing, not completing a job at it’s disposal. This article aims to find out what factors influence university students who participate in organizations doing academic procrastination. This research uses a qualitative method which is carried out by reviewing descriptive literature such as journals. Inclusion criterias in the searching process are (1) research that examines the procrastination factors of university students who participate in organizations, (2) The subject of this study is University Students as the Organizer, (3) research conducted in 2015-2022. Meanwhile, the exclusion criterias are articles that do not meet the inclusion criteria and theses or papers that have not been published as publications. Based on the literature review, The results show the factors that influence the level of procrastination of students who participate in organizations are grouped into two factors: internal and external factors. Internal factors include: tend to have interrole conflict, lack of self-management, poor and disorganized time management, poor self-regulated learning, irrational thoughts, low self-efficacy. Meanwhile, external factors include: high levels of student activity in participating in organizations, the influence of peers or peer groups, having higher conformity with their organizational groups than students who do not join organizations.